1999
DOI: 10.1038/sj.jea.7500036
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure to environmental tobacco smoke: salivary cotinine, airborne nicotine, and nonsmoker misclassification

Abstract: A large study was conducted to assess exposure to environmental tobacco smoke (ETS) in a geographically dispersed study population using personal breathing zone air sampling and salivary cotinine levels. Approximately 100 self-reported nonsmoking subjects in each of 16 metropolitan areas were recruited for this investigation. Cumulative distributions of salivary cotinine levels for subjects in smoking and nonsmoking homes and workplaces exhibited a general trend of decreasing salivary cotinine levels with decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…On the other hand, location -or season -specific cotinine levels exhibited no correlation with CHRYS / BPer ratios, while their correlation with declared ETS exposure was not consistent. However, there is still no general agreement on the degree to which cotinine can serve as a quantitative or semi -quantitative indicator of ETS exposure particularly at low levels of exposure ( Henderson et al, 1989;Coultas et al, 1990a,b;Benowitz, 1999;Jenkins and Counts, 1999 ). In particular, inter-individual differences in the nicotine metabolism may have contributed to the poor quantitative correlation of plasma cotinine with the other ETS -related parameters observed in the present study.…”
Section: Exposure To Ets and Its Influence On Pah Exposure Profilesmentioning
confidence: 53%
“…On the other hand, location -or season -specific cotinine levels exhibited no correlation with CHRYS / BPer ratios, while their correlation with declared ETS exposure was not consistent. However, there is still no general agreement on the degree to which cotinine can serve as a quantitative or semi -quantitative indicator of ETS exposure particularly at low levels of exposure ( Henderson et al, 1989;Coultas et al, 1990a,b;Benowitz, 1999;Jenkins and Counts, 1999 ). In particular, inter-individual differences in the nicotine metabolism may have contributed to the poor quantitative correlation of plasma cotinine with the other ETS -related parameters observed in the present study.…”
Section: Exposure To Ets and Its Influence On Pah Exposure Profilesmentioning
confidence: 53%
“…While data from a study previously conducted by the authors (Jenkins and Counts, 1999;Jenkins et al, 1996 ) have demonstrated little correlation between individual salivary cotinine levels and individual 24-h nicotine exposures, on a group basis, median or mean levels of salivary cotinine are highly correlated with median /mean ETS nicotine exposures. Judging from the group statistics for salivary cotinine in this study, for wait staff and bartenders who live with smokers, exposure to ETS outside the workplace appears to be at least as important as exposure in the workplace.…”
Section: Cotinine Resultsmentioning
confidence: 86%
“…Relying on toenail biomarkers to produce cutoff points for differentiating those exposed to SHS and those not exposed is also problematic because there are no population-based measures of these biomarkers. Attempts by several investigators to use cutoff points for a more widely used biomarker of SHS, such as cotinine, have failed to reach consistent values (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%